2010
DOI: 10.1007/s11240-010-9689-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of efficient and rapid regeneration system for some diploid wild species of Arachis

Abstract: Though peanut tissue culture has advanced to a considerable extent using a number of explants with the subsequent production of transgenic plants, wild Arachis species appeared to be recalcitrant to using similar explants. In this study, the use of cotyledonary nodes as explants prepared from 7-day old seedlings resulted in the development of a simple and rapid regeneration protocol for five diploid wild species including A. diogoi, A. stenosperma, A. duranensis, A. cardenasii and A. correntina belonging to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Even though several studies involving diff erent species have shown that genotype plays a critical role during in vitro regeneration (Bailey et al, 1993;Srinivasan et al, 2010), it is desired that a regeneration protocol be applicable to a wide range of genotypes or even species. The protocols developed in this study were suitable across six diff erent genotypes of A. paraguariensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though several studies involving diff erent species have shown that genotype plays a critical role during in vitro regeneration (Bailey et al, 1993;Srinivasan et al, 2010), it is desired that a regeneration protocol be applicable to a wide range of genotypes or even species. The protocols developed in this study were suitable across six diff erent genotypes of A. paraguariensis.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the induction of tetraploidy is another vital technique that could broaden the available gene pool as well as eliminate hybridization barriers that are due to diff erences in ploidy levels. Interestingly, tissue culture of cultivated peanut has witnessed a remarkable improvement in the past few decades; however, many of the wild Arachis species appear recalcitrant to similar methods (Srinivasan et al, 2010). Specifi cally for A. paraguariensis, limited success has been achieved in the regeneration of plants from mature leafl ets (Dunbar and Pittman, 1992), protoplasts (Li et al,…”
mentioning
confidence: 99%
“…Recombine p2+4ENTR into pCAPD 29 (NCBI Accession: KC176455.1) using LR clonase II enzyme mix according to manufacturer's instructions to make plasmid p5XCAPD, and transform it into Escherichia coli DH5α using standard techniques followed by partial sequencing. Note: The complete RNAi insert is shown in 33 . Move tissues to SIM (500 μM cefotaxime and 100 μM kanamycin) for shoot formation, with bi-weekly transfers for 2 months.…”
Section: Molecular Construct and Peanut Transformationmentioning
confidence: 99%
“…Leaflets are the most widely used explants in peanut tissue culture. Several other types of explants, such as cotyledonary nodes (Srinivasan et al, 2010), epicotyls, hypocotyls (Marion et al, 2008), axillary meristems (Singh and Hazra, 2009) and cotyledons (Bhatnagar et al, 2010; *Corresponding author. E-mail: jzhang@ippcaas.cn.…”
Section: Introductionmentioning
confidence: 99%